Partnerships for human security in fragile contexts: where community safety and security sector reform intersect. Issue 3 (3rd May 2016) - Homel, Peter; Masson, Nicolas
ABSTRACT: Implementing sustainable community safety and security sector reform (SSR) in highly unstable and conflict-affected contexts is a significant and growing challenge. Donor-led SSR processes claim to enable transparent, effective and accountable provision of security. Yet, traditional, externally driven SSR processes implemented in a top-down manner have been shown to have important shortcomings. Using the experience of a form of SSR undertaken in the Jenin Governorate in the Palestinian territories, this article highlights some of these shortcomings—in particular, a lack of local ownership, failure to address governance issues, co-optation of political and security elites, and neglect of citizens' views and needs—as well as describing a viable method for overcoming them to produce a more sustainable approach to community safety in extremely difficult circumstances through the use of outcome-based local crime prevention planning processes. In contrast, the Jenin community safety project was a bottom-up, community-based approach that built effective 'partnerships' for crime prevention with both formal security providers (for example, security forces, executive authorities, parliamentarians and governors' offices) and informal security providers (for example, civil society, the media, and tribal and business leaders) to produce a viable mechanism by which a safer community with stronger local leadership might be created.